Jobs, Poverty, and Working Conditions in South Asia: Regional perspectives on World Development Report 1995 (Washington, D.C. The World Bank, 1995)
This report is a summary of "World Development Report 1995: workers in an integrating world" which deals with labor and employment, issues that are important to South Asia. Indeed, expanding employment and increasing the remuneration of workers, which are crucial for poverty elimination, is the overarching objective for all countries in the region. The report also emphasizes the importance of credibility and of softening the impact of transitions on workers. Finally, the report presents the key messages of " World Development Report 1995 " as they apply to South Asia and discusses the following topics: 1) development challenge; 2) impact of international integration on workers; 3) domestic labor policies; 4) lowering the temporary costs of transition; and 5) the outlook for South Asian workers.
Keywords: Financial literacy